Direct numerical simulations of water flooding process through digitized porous rocks. (November 2019) - Patel, H.V.; Das, S.; Kuipers, J.A.M.; Peters, E.A.J.F.
Highlights: Coupled VOF-IBM method for complex solid geometries in stereolithographic mesh format. Water flooding simulations through digitized rocks of Fontainebleau sandstone. Effect of porosity on oil mobility, viscous finger characteristics and energy budget. Abstract: Water flooding is a secondary oil recovery process where oil from porous rocks is displaced by high pressure water. In this paper we focus on the direct numerical simulation of multiphase flows through complex solid structures with wettability effects using a coupled immersed boundary and volume of fluid method (IBM-VOF). Our method is tested for a wide range of validation/verification cases. The water flooding process through Fontainebleau sandstone is simulated for porosities between 0.15 and 0.25, at representative pore-scale Reynolds and capillary numbers. First, we quantify the temporal change in oil saturation, phase pressure difference and oil/water interstitial velocities to study the mobility of oil through the rocks. Further, we focus on the oil-water interfacial surface area and the specific length scale to study the growth of viscous fingers inside pores. Finally, we evaluate different energies and dissipation rates to understand the energy exchange encountered in the water flooding process.